ความสวยงามวางนัยทัวไป: ผลคูณของสองจานวนที่ทุกหลักเป็นเลข 1: Generalized Beauty: the Product of Two Numbers that Every Digit is 1 - Yotin; Ngamsong, Yuwaret; Iampan, Aiyared (Asian Health, Science and Technology Reports, 2014)